THE IMPACT OF CUSTOMER RELATIONSHIP MANAGEMENT PRACTICES ON CUSTOMER SATISFACTION AND LOYALTY: AN EMPIRICAL STUDY IN VARANASI, UTTAR PRADESH, INDIA - Dr Subhash Pratap Singh (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
Purpose: This study examines the impact of Customer Relationship Management (CRM) practices on customer satisfaction and customer loyalty in the context of Varanasi, Uttar Pradesh, India. Specifically, it evaluates how key CRM dimensions—service responsiveness, personalization, complaint handling, communication quality, technology support, and loyalty programs—influence satisfaction and, in turn, customer loyalty. Design/Methodology/Approach: A cross-sectional survey design was employed. Primary data were collected from customers of retail, banking, and service-sector organizations operating in Varanasi. Using a structured questionnaire with five-point Likert-scale items, 420 valid responses were obtained after data screening. The data were analyzed using Structural Equation Modeling (SEM) and hierarchical regression techniques. Reliability and validity were assessed through Cronbach’s alpha (α ranging from 0.80 to 0.89), Composite Reliability (CR > 0.85), and Average Variance Extracted (AVE > 0.59). Mediation effects were tested using bootstrapping procedures. Findings: The results indicate that CRM practices have a significant positive effect on customer satisfaction (β = 0.69, p < 0.001). Among CRM dimensions, service responsiveness (β = 0.29, p < 0.001), complaint handling (β = 0.21, p < 0.001), and personalization (β = 0.18, p = 0.002) exerted the strongest influence on satisfaction. Customer satisfaction was found to be a strong predictor of customer loyalty (β = 0.56, p < 0.001). Additionally, CRM practices had a direct positive effect on loyalty (β = 0.24, p < 0.001). Mediation analysis confirmed that customer satisfaction partially mediates the relationship between CRM practices and customer loyalty, with a significant indirect effect (β = 0.39; 95% CI: 0.30–0.48). Practical Implications: Organizations should prioritize improving complaint handling mechanisms, enhancing service responsiveness, and implementing personalized customer interactions, supported by effective CRM technology integration, to strengthen satisfaction and loyalty. Originality/Value: This study provides city-level, multi-industry empirical evidence from Varanasi, offering context-specific insights into CRM effectiveness in a tier-2 Indian city setting.